Quantitative Benefit–Risk Assessment of P‐gp–Mediated Drug–Drug Interactions of Dabigatran Coadministered With Pharmacokinetic Enhancers in Patients With Renal Impairment. Issue 1 (10th December 2020) - Lingineni, Karthik; Farhan, Nashid; Kim, Sarah; Cristofoletti, Rodrigo; Gordon, Lori A.; Kumar, Parag; Penzak, Scott; Hadigan, Colleen; George, Jomy M.; Brown, Joshua D.; Schmidt, Stephan
Abstract : Drug–drug interactions (DDIs) between dabigatran and ritonavir/cobicistat are of major concern in people living with HIV, particularly in those with impaired renal function, because they can result in increased dabigatran exposure and thus an increased risk of major bleeding events. However, the extent of this interaction and subsequent need for dose adjustment in subjects with varying degrees of renal function is currently not yet fully understood. To close this knowledge gap, we conducted an integrated population physiologically‐based pharmacokinetic/pharmacodynamic analysis linking changes in dabigatran exposure due to DDIs and varying degrees of renal function to the probability of experiencing an ischemic stroke or major bleeding event within 1 year. The results of our analysis suggest that coadministration of dabigatran etexilate (dabigatran prodrug) and ritonavir/cobicistat should be avoided in subjects with severe renal impairment. A 2‐hour dose separation or dabigatran etexilate dose reduction to 110 mg b.i.d. (twice daily) should be considered in subjects with moderate renal impairment when coadministered with ritonavir, while the dabigatran etexilate dose should be further reduced to 75 mg b.i.d. when coadministered with cobicistat. No dabigatran etexilate dose adjustment is needed in subjects with normal renal function receiving ritonavir, but dabigatran etexilate dose reduction to 110 mg b.i.d. should be considered when coadministered with cobicistat.